#Cuéntalo: the path between archival activism and the social archive(s). Issue 3 (1st September 2020) - Ruiz Gómez, Vicenç; Maria Vallès, Aniol
ABSTRACT: The goal of this article is to explain our experience, as Society of Catalan Archivists and Records Managers (AAC) members, in the field of social web archiving. To that end, we have structured it in three main parts, the first of which is to show the importance of archival science as a political tool in the framework of the information society. The second part focuses on the path followed by the AAC from its first steps taken to preserve social web hashtags, in order to gain technical expertise, to the reflection on the theoretical background required to go beyond the mere collection of social web content that led us to the definition of a new type of archival fonds: the social fonds. Finally, the third part sets out the case study of #Cuéntalo. Thanks to our previous experiences, this hashtag, created to denounce male violence, enabled us to design a more robust project that not only included the gathering and preservation of data but also a vast auto-categorisation exercise using a natural language processing algorithm that assisted in the design of a dynamic and startling data visualisation covering the 160, 000 original tweets involved.